El posicionamiento de las consultoras de ventas por catálogo y su aportación al desarrollo económico–social de los ciudadanos del cantón Quevedo, año 2012 - Ortega Moreira, Karla Mercedes (2015)
Quevedo is the economic hub of the province of Los Rios, is located in a strategic area that connects with the main cities of the country and is a transit zone bound to ports and capitals of most developed provinces of Ecuador. Catalog sales in Quevedo are an important source of income generation for all families and underemployed Canton. It is important to note the important contribution of consultants from catalog sales in the economic and social development of the city. The 45.17% of respondents in the canton purchase Quevedo makes catalogs from different suppliers in a personalized way. The benefits produced by this type of marketing is an important source of employment by 48.56%, so the 81.20% consider that this type of economic activities have contributed to economic and social development of the city, which has led to improved economic and social situation according to 69.97%. The degree of contribution to economic and social development has been seen as high as the 47.78%, while 45.95% think that this has been good. Preference shopping catalog sales has focused on costumes and lingerie with 30.29%, followed by perfume and cosmetics with 29.77%, in the form of cash and credit sales according to 42.82%. To improve performance and productivity, according to the fundamental strategy 24.54% is the variety of products offered, followed by 21.41% with prizes awarded to vendors. The effect of strategies on consumers is considered favorable as the 72.32% of respondents.